Factores psicopedagógicos y su impacto en el rendimiento académico de los estudiantes del 5to año de educación básica de la Unidad Educativa ¨Potosí¨, Urdaneta 2022 - Calderón Chacón, Joselyn Lourdes (2022)
The project is focused on psychopedagogical factors and their impact on the academic performance of students. This seeks to improve the teaching-learning process, considering characteristics and strategies, for the optimization of techniques used in the classroom. The project is based on the lack of knowledge, specifically in students and teachers, related to the pedagogical and the psychosocial. Initially, the conception and definition of the psychopedagogical processes is proposed, exposing its characteristics, strategies and techniques that define it, in order to show the impact on the academic performance of the students. The criteria of academic performance, the types, the relationship it has with the factors are exposed, in order to propose a totally practical strategy so that it can be easily adapted to students for their learning development. Finally, the process of the factors is described and how it influences the academic performance of the students and techniques are proposed so that the proposed objectives are successful in the classroom. A standardization will be carried out that guarantees the viability and quality of the teaching-learning process so that they have precise knowledge about the factors and how they influence their process and be used in the classes taught to improve the pedagogical and psychosocial field, in such a way For students and teachers who are unaware of psychopedagogical factors and their impact on academic performance, consult this project and serve as a guide for future educational institutions.